Ruxolitinib inhibits cytokine production by human lung macrophages without impairing phagocytic ability - Nikola Mantov; Mathilde Zrounba; Mathilde Zrounba; Marion Brollo; S Grassin-Delyle; S Grassin-Delyle; Matthieu Glorion; Matthieu Glorion; Mélanie David; Emmanuel Naline; Philippe Devillier; Philippe Devillier; et al. (Frontiers Media S.A., 2022)
Background: The Janus kinase (JAK) 1/2 inhibitor ruxolitinib has been approved in an indication of myelofibrosis and is a candidate for the treatment of a number of inflammatory or autoimmune diseases. We assessed the effects of ruxolitinib on lipopolysaccharide (LPS)- and poly (I:C)-induced cytokine production by human lung macrophages (LMs) and on the LMs' phagocytic activity.Methods: Human LMs were isolated from patients operated on for lung carcinoma. The LMs were cultured with ruxolitinib (0.5 × 10−7 M to 10-5 M) or budesonide (10-11 to 10-8 M) and then stimulated with LPS (10 ng·ml−1) or poly (I:C) (10 μg·ml−1) for 24 h. Cytokines released by the LMs into the supernatants were measured using ELISAs. The phagocytosis of labelled bioparticles was assessed using flow cytometry.Results: Ruxolitinib inhibited both the LPS- and poly (I:C)-stimulated production of tumor necrosis factor alpha, interleukin (IL)-6, IL-10, chemokines CCL2, and CXCL10 in a concentration-dependent manner. Ruxolitinib also inhibited the poly (I:C)- induced (but not the LPS-induced) production of IL-1ß. Budesonide inhibited cytokine production more strongly than ruxolitinib but failed to mitigate the production of CXCL10. The LMs' phagocytic activity was not impaired by the highest tested concentration (10-5 M) of ruxolitinib.Conclusion: Clinically relevant concentrations of ruxolitinib inhibited the LPS- and poly (I:C)-stimulated production of cytokines by human LMs but did not impair their phagocytic activity. Overall, ruxolitinib's anti-inflammatory activities are less intense than (but somewhat different from) those of budesonide-particularly with regard to the production of the corticosteroid-resistant chemokine CXCL-10. Our results indicate that treatment with a JAK inhibitor might be a valuable anti-inflammatory strategy in chronic obstructive pulmonary disease, Th1-high asthma, and both viral and non-viral acute respiratory distress syndromes (including coronavirus disease 2019).